A peptide-based aggregation-induced emission bioprobe for selective detection and photodynamic killing of Gram-negative bacteria. (4th November 2020) - Bao, Pingping; Li, Cong; Ou, Hanlin; Ji, Shenglu; Chen, Yao; Gao, Jing; Yue, Xin; Shen, Jing; Ding, Dan
Abstract : A bioprobe with aggregation-induced emission characteristics is developed, which can visualize and photodynamically ablate Gram-negative bacteria in a selective manner. Abstract : Herein, we report a new bioprobe with aggregation-induced emission (AIE) characteristics by conjugation of a far-red/near-infrared emissive AIE luminogen and two polymyxinB peptides. Due to the strong binding effect between polymyxin B and the lipopolysaccharide in the cell wall of Gram-negative bacteria, the bioprobe can selectively visualize Gram-negative bacteria and effectively kill them via photodynamic treatment.